Correlation between thrombocytopenia and adverse outcomes in patients with atrial fibrillation: a systematic review and meta-analysis - Ding, Qiuhua; Xu, Wenlin; Chen, Yaoyao; Chang, Sijie; Zhang, Jinhua (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThrombocytopenia is often associated with adverse outcomes in patients with atrial fibrillation. Therefore, we conducted a meta-analysis to comprehensively assess the impact of thrombocytopenia on ischemic stroke/systemic embolism, major bleeding and all-cause mortality in patients with atrial fibrillation.MethodsTwo electronic databases, PubMed and Web of Science, were systematically searched from their inception to December 1, 2023, including the studies on the correlation between atrial fibrillation patients with thrombocytopenia and adverse outcomes. Relevant data was extracted, literature quality was evaluated, meta-analysis was performed by using REVMAN 5.4 software, and the results were reported with odds ratio (OR) of 95% confidence interval (CI).ResultsA total of 12 studies included 73,824 patients with atrial fibrillation (average age: 72.67, males: 42,275, 57.3%), among them, there were 7,673 patients combined with thrombocytopenia. The average follow-up time of these studies was 87 days to 55 months. Compared to no thrombocytopenia, atrial fibrillation patients combined with thrombocytopenia have a significant risk reduction of ischemic stroke/systemic embolism [OR: 0.79, 95% CI: (0.69, 0.91); P < 0.01]. Nevertheless, the risk of both major bleeding [OR: 1.51, 95% CI: (1.20, 1.79), P < 0.01] and all-cause mortality [OR: 1.40, 95% CI: (1.23, 1.61); P < 0.01] is significantly higher in thrombocytopenia group.ConclusionsThrombocytopenia has an important impact on the prognosis of patients with atrial fibrillation. Thrombocytopenia is significantly associated with a lower risk of ischemic stroke/systemic embolism but a higher risk of major bleeding and all-cause mortality. Attention to thrombocytopenia and optimization of treatment may be the effective way to improve the prognosis of atrial fibrillation with thrombocytopenia.Systematic Review Registrationhttps://www.crd.york.ac.uk/, PROSPERO Registration Number: (CRD42023459916).